Формирование ключевых компетенций на уроках русского языка - Sushech L. G. (Образование и наука в современных условиях, 2015)
This article discusses methods of formation of key competencies at Russian lessons . The basis of this formation is the use of modern educational technologies .
Keywords: русский язык; ключевые компетенции; современные приемы; обучение школьников; key competences; modern methods; teaching students the Russian language